The Maintenance Contract in the new European Contract Law and in the Spanish Law - Vaquer Aloy, Antoni (Iuris Dictio, 2017)
The following article refers to an atypical but highly utilized contract in contemporary civil law: the maintenance contract, which, under Spanish law (and in most legal systems), lacks specific regulations. Using the Draft Common Frame of Reference for private European law, as well as related jurisprudence and legal theories, this article intends to analyze aspects such as duties of collaboration between the parties, conformity of the provision, and contractual risks.
Keywords: Maintenance Contract; Processing Contract; European Contract Law; Draft Common Frame of Reference; Principles of European Law Services Contracts